THE MANAGEMENT OF LANGUAGE LABORATORY IN IMPROVING STUDENTS ARABIC COMPETENCE - Wahyudi Buska; Mukhtar Latif; Risnita Risnita; Kasful Anwar Us; Yogia Prihartini (Arabi : Journal of Arabic Studies, 2020)
This study aimed to describe the success of the management of a language laboratory in improving students’ Arabic language competence. This was a qualitative descriptive study. The research findings show that the language learning process through the laboratory increased the students’ listening and speaking skill. The language learning process through the laboratory was supported by extracurricular activities. This activity also had a positive impact on language learning achievement of students who previously did not understand Arabic. Then, laboratory as a place for accommodating students’ talent such as laboratories was very helpful for students in the learning process; this was because the students could communicate directly with native speakers. The implementation of the development of teaching and learning activities using the Arabic language laboratory was directed to students through inservice training programs. The evaluation program was conducted by Arabic language lecturers to see the level of achievement obtained by students after finishing studying in two ways, namely competitive and non-competitive.